The Relationship Between Knowledge And Attitude Towards The Preventive Behaviors For The Covid-19 Transmission In Pregnant Mothers At “Rini K” Independent Midwifery Practice (PMB), Jagakarsa, South Jakarta, 2021 - Kundaryanti, Rini; Karningsih, Karningsih; Astri, Hetty; Syafrudin, Syafrudin (STRADA : Jurnal Ilmiah Kesehatan, 2021)
<p style="color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">The pregnant mothers’ knowledge and attitude towards Covid-19 transmission prevention are still categorized as poor so pregnant mothers need to know about preventing Covid-19 transmission. This study aimed to know the relationship between knowledge and attitude towards the preventive behaviors for the Covid-19 transmission in pregnant mothers. This study used a cross-sectional approach. The samples were 73 1st trimester pregnant mothers as the respondents. The data collection was done using a questionnaire that passed the validity and reliability test. Respondents who behaved well 51 (69.9%), had good knowledge 40 (54.8%) and who had a positive attitude 30 (41.1%) and a p value of 0.05 on the knowledge and attitude variables. There is a relationship between knowledge and attitudes towards the behavior of preventing the transmission of Covid-19 in pregnant women.